Performance contributing match and game variables in elite and youth badminton players - Loon, Leong Kah (Pusat Pengajian Kesihatan, 2015)
The aim of this study was to investigate the difference of the game structure and playing pattern between the Elite Level and Youth Level badminton players. A total of 14 matches including Semi-finals and Finals of International tournaments were selected. □ The game structure variables selected for this study included match duration, game duration, rallies per game, shots per rally, rally length, rest time between rallies, ball in play in seconds, ball in play in percentage and work to rest ratio. Shots type and shot outcome were chosen for performance indicators of playing pattern. Independent Sample T-test was used for the comparison of all variables between the Elite Level and Youth Level categories. There were statistically significant differences among the categories in match duration, game duration, shots per rally, ball in play in seconds, rally length, and rest time between rallies (p<0.05). There were significant differences in mean distribution of lift shot, net shot, drop shot, lob shot and smash shot between the Elite Level and Youth Lex el categories (p<0.05). In shot outcome, smash shot is the most successful shot with the highest number of w inners while net shot ended up with the highest number of errors. Youth Lexel category had more winners and also errors compared to Elite Level but not significantly different. Iii conclusion, there were differences in the game structure between the Elite Level and Youth Level categories of players. The information can help in improving the technical and tactical skills of the badminton players up to the international level.